Beware those flip-flopping Europeans! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
We had some alienated responses from European readers about recent articles in Spore about the growing market for insects as a food. So what? , we said to ourselves; insects are a regular part of the ACP diet and informal economy, with a US$ 2...